2007
DOI: 10.1073/pnas.0703976104
|View full text |Cite
|
Sign up to set email alerts
|

Bak regulates mitochondrial morphology and pathology during apoptosis by interacting with mitofusins

Abstract: Mitochondrial injury, characterized by outer membrane permeabilization and consequent release of apoptogenic factors, is a key to apoptosis of mammalian cells. Bax and Bak, two multidomain Bcl-2 family proteins, provide a requisite gateway to mitochondrial injury. However it is unclear how Bax and Bak cooperate to provoke mitochondrial injury and whether their roles are redundant. Here, we have identified a unique role of Bak in mitochondrial fragmentation, a seemingly morphological event that contributes to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
328
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(346 citation statements)
references
References 46 publications
13
328
1
4
Order By: Relevance
“…However, the mechanism by which they induce apoptosis may differ. It has been previously shown that BAK, but not BAX, plays an important role in mitochondrial fragmentation, a morphological change that facilitates MOMP during apoptosis (35). Here we describe a second unique function for BAK in apoptosis, namely regulation of ceramide generation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the mechanism by which they induce apoptosis may differ. It has been previously shown that BAK, but not BAX, plays an important role in mitochondrial fragmentation, a morphological change that facilitates MOMP during apoptosis (35). Here we describe a second unique function for BAK in apoptosis, namely regulation of ceramide generation.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, ceramides induce negative curvature and lateral phase separation in giant liposomes leading to their fragmentation (45). Thus, ceramide generation may change membrane curvature to facilitate BAK-induced mitochondrial fragmentation in parallel with the inhibition of mitochondrial fusion machinery as has been previously described (35).…”
Section: Discussionmentioning
confidence: 96%
“…Other groups reported similar findings, while ablation of Drp1 was also shown to reduce cytochrome c release (Breckenridge et al, 2003;Brooks et al, 2007;Germain et al, 2005;Lee et al, 2004;Neuspiel et al, 2005). The role of mitochondrial fragmentation in the progression of apoptosis has also been investigated by inhibiting fission through enforced fusion.…”
Section: Accepted M Manuscriptmentioning
confidence: 84%
“…Bak has been shown to interact with Mfn1 and Mfn2, while Bax promotes the activity of Mfn2 (Brooks et al, 2007, Karbowski et al, 2006. In addition, Bcl-2 family members may interact with other cellular proteins that modulate mitochondrial morphology and distribution within the cell.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…However, recent studies suggest that Bak acts upstream of Bax in promoting mitochondrial apoptosis (25,45), and that Bak plays the central role in apoptosis of differentiated neurons (24). Moreover, Bak may play an exclusive role in oxidative stress-mediated apoptosis in the brain (25), and also in mitochondrial fragmentation (45).…”
Section: Discussionmentioning
confidence: 99%